APPLICATION OF STATISTICAL DECISION THEORY TO THE VALUE OF MANAGEMENT INFORMATION PRICE OF OIL AND GAS ENTERPRISES - Витвицька, Оксана Миколаївна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This article describes the possibility of application of statistical decision theory to the value of information price, used in managing of oil and gas enterprises to increase the efficiency of management. The method of the average risk function application was applied. The function helps to establish the value of geophysical information and economic information that regards market conjuncture services.